Human rights under state-enforced religious family laws in Israel, Egypt, and India - Sezgin, Yüksel (Cambridge studies in law and society, 2013)
Introduction -- Personal status, nation-building, and the postcolonial state -- The impact of state-enforced personal status laws on human rights -- A fragmented confessional system: state-enforced religious family laws and human rights in Israel -- A unified confessional system: state-enforced religious family laws and human rights in Egypt -- A unified semi-confessional system: state-enforced religious family laws and human rights in India -- Conclusion: upholding human rights under religious legal systems.